Attack of the kraken - Sherry, Kevin (Sherry, Kevin. Yeti files, 2016)
The merfolk of Atlantis have called in yeti Blizz Richards and his team of cryptozoologists to capture the kraken that is attacking their city, but when he starts to investigate, Blizz realizes that there is a lot the merfolk are not telling him--and something fishy is definitely going on.